Predictors of the feeling of stress in the aviation sector - Magdalena Ślazyk-Sobol; Małgorzata Dobrowolska; Maria Flakus (Nofer Institute of Occupational Medicine, 2021)
Background Employees in the aviation sector constitute an especially interesting professional group due to a lack of empirical data on their psychological functioning, and the fact that this industry is currently experiencing a phase of dynamic development. However, taking into consideration the automation and specific qualities of the sector, human resources should be given much more attention as they are constantly challenged and face diverse difficulties at work while cooperating in various organic and non-organic teams. Material and Methods The study included 326 employees of Pyrzowice (Poland), Szymany (Poland), and Košice (Slovakia) airports (however, people employed at the Polish airports were predominant, N = 250). The average age of the participants was 39.3 years, and the sample was predominantly male (N = 278, 85.3%). During the research procedure, the following questionnaires were used: the Feeling of Threat in the Workplace Questionnaire , the Feeling of Stress Questionnaire , the 10-Item Personality Inventory , and the Mini-COPE Stress Inventory . Results The regression analysis indicated that personality variables did not allow for predicting the level of stress. However, the helplessness-oriented style (β = 0.191, p = 0.004), avoidant behaviors (β = 0.244, p < 0.001), and the feeling of threat (β = 0.147, p = 0.009) were significant predictors of the feeling of stress, and their high level corresponded with a higher level of stress. The final model explained 23% of the total variance in the feeling of stress. Conclusions Based on the results, practical recommendations should concern developing employees' skills related to monitoring stressors and strengthening proactivity in difficult or threatening situations. Such proactive strategies may decrease the tendency to use avoidant and helplessness-oriented behaviors that may cause a higher level of stress perceived by employees. Also, the authors recommend providing training and support using some cognitive behavioral techniques because it seems that the regular application of those methods supports the development of agency and control while facing challenging situations. Med Pr. 2021;72(5):467-77